1995
DOI: 10.1103/physrevb.51.7942
|View full text |Cite
|
Sign up to set email alerts
|

Origin of magic angular momenta in few-electron quantum dots

Abstract: We show the effect of quantum-mechanical symmetry on determining the features of two-dimensional few-electron quantum dots, and thereby elucidate the origin of the magic numbers.Recent advances in microfabrication have allowed the creation of quantum dots in semiconductor heterostructures by laterally confining two-dimensional electrons. The confining potential is, to a good approximation, parabolic and a small number ji/ (N=1,2,3, . . . ) of electrons per dot has been achieved experimentally. ' The electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
100
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 3 publications
4
100
0
Order By: Relevance
“…Such studies (both EXD and variational) revealed that, at least for finite systems, the underlying physical picture governing the behavior of strongly-correlated electrons is not that of a "quantum liquid." Instead, the appropriate description is in terms of a "quantum crystal," with the localized electrons arranged in polygonal concentric rings [19,20,21,22,23,25,26,27]. These "crystalline" states lack [21,23] the familiar rigidity of a classical extended crystal, and are better described [19,20,21,22,23,24] as rotating electron ( or Wigner) molecules (REMs or RWMs).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies (both EXD and variational) revealed that, at least for finite systems, the underlying physical picture governing the behavior of strongly-correlated electrons is not that of a "quantum liquid." Instead, the appropriate description is in terms of a "quantum crystal," with the localized electrons arranged in polygonal concentric rings [19,20,21,22,23,25,26,27]. These "crystalline" states lack [21,23] the familiar rigidity of a classical extended crystal, and are better described [19,20,21,22,23,24] as rotating electron ( or Wigner) molecules (REMs or RWMs).…”
Section: Introductionmentioning
confidence: 99%
“…Our study leads to the following two main results: (i) in analogy with 3D natural molecules, the WM's can rotate and the restoration of the total-spin and rotational symmetries via projection techniques describes their lowest rotational bands (yrast bands 14,34 ) in addition to the ground state, and (ii) the lowering of the symmetry, which results in the (discrete) point-group symmetry of the UHF wave function, underlies the appearance of the sequences of magic angular momenta (familiar from exact-diagonalization studies [35][36][37][38][39][40] ) in the excitation spectra of single QD's. Since exact-diagonalization methods are typically restricted to small sizes with N ≤ 10, the present two-step method of breakage and subsequent restoration of symmetries offers a promising new avenue for accurately describing larger 2D electronic systems.…”
mentioning
confidence: 99%
“…In this section, we will not proceed any further with explicit numerical or analytic derivations of additional RBS wave functions. Instead, we will use the RBS approach to illustrate through a couple of concrete examples how certain universal properties of the exact solutions, i.e., the appearance of magic angular momenta in the exact rotational spectra, [35][36][37][38][39][40] relate to the symmetry broken UHF solutions. Indeed, we will demonstrate that the magic angular momenta are a direct consequence of the symmetry breaking at the UHF level and that they are determined fully by the molecular symmetries of the UHF determinant.…”
mentioning
confidence: 99%
“…A cyclic coordinate permutation is a π/3 rotation such that Ψ → exp (πiM/3)Ψ. In this case Ψ changes sign [25], and therefore M = 6p + 3 (p integer) and odd parity. Our findings show that an excited magic state can be created adding L quanta of angular momentum to the ground state via the density fluctuation operator ρ † L .…”
mentioning
confidence: 99%